2001
DOI: 10.1074/jbc.m007701200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Alcohol Oxidase/RNA-binding Protein with Affinity for Mycovirus Double-stranded RNA from the Filamentous FungusHelminthosporium (Cochliobolus)victoriae

Abstract: We have cloned and sequenced a novel alcohol oxidase (Hv-p68) from the filamentous fungus Helminthosporium (Cochliobolus) victoriae that copurifies with mycoviral double-stranded RNAs. Sequence analysis revealed that Hv-p68 belongs to the large family of FADdependent glucose methanol choline oxidoreductases and that it shares significant sequence identity (>67%) with the alcohol oxidases of the methylotrophic yeasts. Unlike the intronless alcohol oxidases from methylotrophic yeasts, a genomic fragment of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
(60 reference statements)
1
28
0
Order By: Relevance
“…Genes encoding AOX have thus far been identified, and cDNAs have been cloned from several yeasts (38,44,51) and mold fungi (27,44,48,49). Here we present for the first time the primary structure of AOX from a basidiomycete fungus that compared to the yeast and/or mold enzymes exhibited some unique features.…”
Section: Discussionmentioning
confidence: 93%
“…Genes encoding AOX have thus far been identified, and cDNAs have been cloned from several yeasts (38,44,51) and mold fungi (27,44,48,49). Here we present for the first time the primary structure of AOX from a basidiomycete fungus that compared to the yeast and/or mold enzymes exhibited some unique features.…”
Section: Discussionmentioning
confidence: 93%
“…Total RNA was extracted from virusinfected or vector-transformed fungal mycelia using TRIzol reagent (Invitrogen) according to the manufacturer's protocol. The full-length plus-stranded RNA transcript of HvV190S (ϳ5.2 kb) was synthesized in vitro using T7 RNA polymerase and plasmid pT7HvV190S containing full-length HvV190S cDNA as template (23,46). RNA samples (15 g) were then fractionated on a denaturing agarose gel.…”
Section: Methodsmentioning
confidence: 99%
“…In the production of AODs by filamentous fungi, Ko et al have recently reported that Thermoascus aurantiacus NBRC 31963 inductively produced two AODs by incubation with the pectin medium, and characteristics of both enzymes have been revealed by his group (Ko et al, 2005). The genes showing a high homology to AODs from methylotrophic yeasts have also been isolated from a few filamentous fungi (Holzmann et al, 2002;Segers et al, 2001;Soldevila and Ghabrial, 2001), but their proteins have not been purified.…”
Section: Introductionmentioning
confidence: 99%